1998
DOI: 10.1007/s004170050038
|View full text |Cite
|
Sign up to set email alerts
|

Strontium plaque irradiation of subfoveal neovascular membranes in age-related macular degeneration

Abstract: Local low-energy beta irradiation with a strontium-90 applicator can induce regression of choroidal neovascularization. The effect of irradiation is seen as a decrease in the size of the choroidal neovascular membrane and disappearance of the neurosensory detachment and exudates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
0
23
0
6
Order By: Relevance
“…The visual results at 12 months have been described in detail previously (Jaakkola et al 1998). At the 24-month examination VA of the treated eyes ranged from 0.25 to ∞0.03, with a mean VA of 0.06.…”
Section: Visual Acuitymentioning
confidence: 94%
See 2 more Smart Citations
“…The visual results at 12 months have been described in detail previously (Jaakkola et al 1998). At the 24-month examination VA of the treated eyes ranged from 0.25 to ∞0.03, with a mean VA of 0.06.…”
Section: Visual Acuitymentioning
confidence: 94%
“…All eyes received a radiation dose of 15 Gy at a depth of 1.75 mm, as previously described (Jaakkola et al 1998). The mean age of the patients at the time of treatment was 75 years (range 63-84 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studien zur primären episkleralen Brachytherapie bei AMD sind mit StrontiumApplikatoren ( 90 Sr/ 90 Y) [17,18] und Palladium-Applikatoren ( 103 Pa) [9,10] durchgeführt worden; 106 Ru/ 106 Rh-Applikatoren sind vereinzelt eigesetzt worden, ohne dass daraus eindeutige Daten abzuleiten wären [29].…”
Section: Episklerale Brachytherapieunclassified
“…Brachytherapy has utilised either palladium-103 ( 103 P), a low-energy gamma emitter, or 90 Sr. Studies have reported doses of between 500 and 2400 cGy to the target tissue. 52,53 Dosimetric studies have demonstrated that a local approach leads to a considerably smaller radiation dose to the lens and optic nerve than for external beam therapy. When these doses are administered by an external beam, the dose given to the lens may be sufficient to induce cataract, as up to 50% of the maximum dose may fall on the posterior lens.…”
Section: Pterygiummentioning
confidence: 99%